Behavior and biochemical responses of the polychaeta Hediste diversicolor to polystyrene nanoplastics - Silva, M.S.S. (2022)
Plastic debris has been reaching the world's oceans since it started being used. Multiple studies have been addressing the effects of microplastics in various organisms but, despite the increased scientific awareness, there is still a significant gap in knowledge when it comes to small-sized plastic particles of sizes below 100 nm. The aim of this study was to understand the effect of waterborne 100 nm polystyrene nanoplastics (PS NPs) on the marine polychaeta Hediste diversicolor, a keystone species in intertidal and coastal environments, in terms of behavior, neurotransmission, oxidative status, energy metabolism and oxidative damage. Results of PS NPs characterization showed an aggregation along the time and with increasing concentrations. Results also revealed a considerable impact of PS NPs on ecologically relevant endpoints like cholinesterase (ChE) and burrowing, but no increases in most of the parameters associated with oxidative stress. Protein carbonylation was found to be more sensitive to PS NPs effects than lipid peroxidation. Behavioral alterations induced by PS NPs may affect nutrient cycling and (endo-)benthic fauna. The data revealed in this study highlighted the potential consequences of NPs to benthic organisms and the need for further studies.